2001
DOI: 10.1097/00075198-200108000-00015
|View full text |Cite
|
Sign up to set email alerts
|

New ways to reduce unnecessary variation and improve outcomes in the intensive care unit

Abstract: The care of critically ill patients and the advent of the modern day intensive care unit (ICU) present a large person power and cost burden to society. The high cost of critical care is attributed to high overhead expenses (eg, experienced staff and equipment), high resource utilization (eg, pharmaceutical resources, lab testing, imaging procedures), and high demand for services. Pathways to standardize numerous facets of patient care have been shown to improve the efficiency of delivery of care and to reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 37 publications
0
47
0
6
Order By: Relevance
“…[17][18][19] Furthermore, it has been reported that protocol-based therapies may enhance and maintain the quality and efficiency of care thereby resulting in decreased morbidity and mortality. 17,18 The high response rate to this survey suggests a general motivation of physicians from both the HSCT and PCCM services to improve the outcomes of the critically ill pediatric HSCT patient. Such motivation will clearly be needed to establish clinical guidelines and protocolized treatment plans.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Furthermore, it has been reported that protocol-based therapies may enhance and maintain the quality and efficiency of care thereby resulting in decreased morbidity and mortality. 17,18 The high response rate to this survey suggests a general motivation of physicians from both the HSCT and PCCM services to improve the outcomes of the critically ill pediatric HSCT patient. Such motivation will clearly be needed to establish clinical guidelines and protocolized treatment plans.…”
Section: Discussionmentioning
confidence: 99%
“…1,11,30,31,40,43,45 Integrating cost analysis into the assessment of clinical pathways and care processes may reveal expensive steps or activities that do not add value to patient care as well as significant cost differences that could translate into potentially unnecessary process variation. 19,36 Furthermore, linking cost analysis to the implementation of improvement measures and redesign initiatives has become critical to ensure that outcomes are being improved and costs are being simultaneously contained or reduced to optimize the delivery of value-based care. 23,40,41,45 The time-driven ABC (TD-ABC) method, described by Kaplan and colleagues, has been gaining popularity in health economics as a costing methodology with the potential to support value-optimization initiatives.…”
Section: Assessing Cost Of Care Deliverymentioning
confidence: 99%
“…Quelle: nach Pronovost et al 2001a;Randolph/Pronovost 2002;Holcomb et al 2001;Carlson et al 1996, adaptiert …”
Section: Angemessenheit Der Intensivversorgungunclassified
“…B. Entwöhnung von der Beatmung, Umgang mit Sedativen oder der Transfusion (Holcomb et al 2001;Morris 2001;Wall et al 2001;Randolph/Pronovost 2002;Brattebo et al 2002).…”
Section: Rekrutierung Von Organspendernunclassified